Backside calibration chronopotentiometry: using current to perform ion measurements by zeroing the transmembrane ion flux - Xu, Y.; Ngeontae, W.; Pretsch, E.; Bakker, Eric (American Chemical Society, 2008)
A recent new direction in ion-selective electrode (ISE) research utilizes a stir effect to indicate the disappearance of an ion concentration gradient across a thin ion-selective membrane. This zeroing experiment allows one to evaluate the equilibrium relationship between front and backsidesolutions contacting the membrane by varying the backside solution composition. This method is attractive since the absolute potential during the measurement is not required, thus avoiding standard recalibrations from the sample solution and a careful control of the reference electrode potential. We report here on a new concept to alleviate the need to continuously vary the composition of the backside solution. Instead, transmembrane ion fluxes are counterbalanced at an imposed critical current.A theoretical model illustrates the relationship between the magnitude of this critical current and the concentration of analyte and countertransporting ions and is found to correspond well with experimental results. The approach is demonstrated with lead(II)-selective membranes and protons as dominating interference ions, and the concentration of Pb2+ was successfully measured in tap water samples. The principle was further evaluated with calcium-selective membranes and magnesium as counterdiffusing species, with good results. Advantages and limitations arising from the kinetic nature of the perturbation technique are discussed.